A Flexible Reversed Multicast Tag Collective Scheme in Base Station Wireless Network - Dong Zhiling; Zhu Yonghua; Yao Hong; Pan Shunhong; Wang Yifei (2008 4th International Conference on Wireless Communications, Networking and Mobile Computing, 2008)
Select the close-to-optimal collective algorithm based on the parameters of the collective call at the run time is an important step in achieving good performance of collective operation in base station wireless network. In this paper, we present our Reversed Multicast Tag Collective (RMTC) scheme to optimize the collective routing in base station wireless network. We verify our mechanism in a simulation platform which is implemented according to the message passing mechanism of base station wireless network and analyze the result and expect run time performance penalty. The results indicate that our Reversed Multicast Tag Collective scheme is flexible and feasible in base station wireless network with its high efficiency and wide applicability.